The relationship between organizational justice and bullying behaviors among nurses: the role of nurse managers' caring behaviors - Ebtsam Aly Abou Hashish; Sharifa Alsayed; Hend Abdu Alnajjar; Siti Awa Abu Bakar (BMC, 2024)
Abstract Background Organizational justice is pivotal in fostering a fair and supportive workplace culture, which strengthens the connections between managers and nurses, among nurses themselves, and ultimately, between nurses and their patients. Assessing the perceived levels of organizational justice and managerial behaviors can identify key areas for improving nurses' commitment and loyalty, while simultaneously reducing incidents of workplace bullying. Purpose This study aims to investigate how bedside nurses perceive organizational justice, nurse managers' caring behaviors, and their exposure to workplace bullying. Additionally, it seeks to explore the relationship between organizational justice, nurse managers' caring behaviors, and nurses' perceived exposure to workplace bullying. Methods A descriptive-correlational study was conducted in the inpatient care unit of a Saudi hospital. A convenience sample of 256 nurses participated, completing the Organizational Justice Questionnaire (OJQ), the Caring Factor Survey: Caring of the Manager (CFS-CM), and the Negative Acts Questionnaire-Revised (NAQ-R). The collected data were analyzed using descriptive statistics and regression analysis. Results Descriptive statistics revealed moderate levels of perceived organizational justice and managerial caring behaviors among nurses, alongside low reported exposure to workplace bullying. Significant correlations were found among the studied variables, indicating that higher perceived organizational justice was associated with higher managerial caring and lower workplace bullying (p < 0.05). Mediation analysis demonstrated a significant indirect effect of organizational justice on workplace bullying through the mediating role of nurse managers' caring behaviors (a×b = -0.0652, p < 0.001). Furthermore, the direct effect of organizational justice on workplace bullying remained significant even when accounting for the mediator (c = -0.5509, p < 0.001). Conclusion This study highlights the vital role of organizational justice and managerial caring in cultivating a positive work environment and mitigating workplace bullying. Implementing clear policies and procedures while promoting fairness and equality in resource allocation, decision-making processes, and interactions are essential strategies for fostering positive attitudes and work behaviors among nurses.